2003
DOI: 10.1103/physrevb.67.205407
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic spin magnetization of strongly correlated two-dimensional electrons in a silicon inversion layer

Abstract: A novel method, invented to measure the minute thermodynamic magnetization of dilute two dimensional fermions, is applied to electrons in a silicon inversion layer. The interplay between the ferromagnetic interaction and disorder enhances the low temperature susceptibility up to 7.5 folds compared with the Pauli susceptibility of non-interacting electrons. The magnetization peaks in the vicinity of the density, where transition to strong localization takes place. At the same density, the susceptibility approac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
171
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(188 citation statements)
references
References 30 publications
15
171
2
Order By: Relevance
“…In the highly interacting, dilute regime (r s > ∼ 3), χ * and m * are typically enhanced compared to the band values and increase with increasing r s , as confirmed both theoretically [1][2][3][4][5][6][7][8] and experimentally. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Besides r s , the spin and/or valley degrees of freedom also play an important role in the re-normalization of m * and χ * since they modify the exchange interaction. 5,6,17,[24][25][26][27] In particular, it was recently demonstrated that when a 2D electron system is fully spin and valley polarized, m * is suppressed compared to its band value.…”
mentioning
confidence: 99%
“…In the highly interacting, dilute regime (r s > ∼ 3), χ * and m * are typically enhanced compared to the band values and increase with increasing r s , as confirmed both theoretically [1][2][3][4][5][6][7][8] and experimentally. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Besides r s , the spin and/or valley degrees of freedom also play an important role in the re-normalization of m * and χ * since they modify the exchange interaction. 5,6,17,[24][25][26][27] In particular, it was recently demonstrated that when a 2D electron system is fully spin and valley polarized, m * is suppressed compared to its band value.…”
mentioning
confidence: 99%
“…2, 12, and 13 The electron density where we find spin polarization in the wire is roughly equal to what has been determined experimentally in GaAs/ AlGaAs. 12,13 Direct measurements of the magnetization of the 2DEG in Si-SiO 2 heterostructures suggests an increased spin susceptibility 18,19 close to the MIT but it is not clear in these experiments whether a spin polarized phase, as we find, exists.…”
Section: Discussionmentioning
confidence: 38%
“…By modulating an in-plane magnetic field and measuring the minute current between gate and 2DEG the thermodynamic magnetization of the 2DEG is found through Maxwell's equations. 18,19 Both Prus et al 18 and Shaskin et al 19 find that the spin susceptibility is critically enhanced prior to the metal-insulator transition in the 2DEG. It is, however, not clear from the experiment whether a spin polarized phase actually exists between the metal and insulating phase or if there is only an increased magnetization in the metallic phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations